Point Prevalence Survey of Acute Hospital Patients with Difficulty Swallowing Solid Oral Dose Forms - Anne Harnett; Stephen Byrne; Jennifer O'Connor; Eimear Burke; Laura South; Declan Lyons; Laura J. Sahm (MDPI AG, 2024)
The safe administration of solid oral dose forms in hospital inpatients with swallowing difficulties is challenging. The aim of this study was to establish the prevalence of difficulties in swallowing solid oral dose forms in acute hospital inpatients. A point prevalence study was completed at three time points. The following data were collected: the prevalence of swallowing difficulties, methods used to modify solid oral dose forms to facilitate administration, the appropriateness of the modification, and patient co-morbidities. The prevalence of acute hospital inpatients with swallowing difficulties was an average of 15.4% with a 95% CI [13.4, 17.6] across the three studies. On average, 9.6% of patients with swallowing difficulties had no enteral feeding tube in situ, with 6.0% of these patients receiving at least one modified medicine. The most common method of solid oral dose form modification was crushing, with an administration error rate of approximately 14.4%. The most common co-morbid condition in these patients was hypertension, with dysphagia appearing on the problem list of two (5.5%) acute hospital inpatients with swallowing difficulties. Inappropriate modifications to solid oral dose forms to facilitate administration can result in patient harm. A proactive approach, such as the use of a screening tool to identify acute hospital inpatients with swallowing difficulties, is required, to mitigate the risk of inappropriate modifications to medicines to overcome swallowing difficulties.